Integrasi Pembelajaran IPA dan Citizen Science: Upaya Peningkatan Literasi Iklim Generasi Muda - Kuntari, Diyah Ayu; Siswanto, Joko (PGRI Kota Semarang, 2025)
Climate change is a global challenge that has a widespread impact and requires understanding and concrete action, especially from the younger generation as the drivers of change in the future. In the context of teaching natural sciences, the application of a citizen science approach provides opportunities for students to be directly involved in observing, collecting, and analyzing environmental data related to climate change. This study uses a literature review method to examine the role of integrating science education with citizen science in improving understanding of climate change among the younger generation. The findings show that this integration successfully improves students' conceptual understanding, critical thinking skills, enthusiasm for learning, and environmental awareness in a relevant context. Although there are challenges such as time constraints, teacher training, and data quality, the use of digital technology and institutional support can reduce these obstacles. The integration of science in science education not only enhances the learning experience but also builds the character and ability of the younger generation to play a responsible role in climate change mitigation and adaptation. This strategy is very much in line with the demands of 21st-century education and sustainable development plans.